Best Practice Peningkatan Keaktifan dan Hasil Belajar Pendidikan Agama Islam dengan Metode Numbered Head Together - Asmuki, Asmuki; Djuwairiyah, Djuwairiyah (Universitas Muhammadiyah Makassar, 2024)
The Numbered Head Together (NHT) method has been widely applied by teachers and researchers. NHT is widely used by them with regard to improving learning outcomes, which is sometimes called learning achievement, sometimes it is also used to increase learning activity or learning activities. Not many have written NHT in the context of increasing activity and learning outcomes together in Islamic Religious Education (PAI) subjects. Therefore, this article is constructed to provide a conceptual overview of increasing activeness and learning outcomes in PAI through NHT. The method used is a literature study of the benefits and advantages of the NHT method and its learning steps combined with PAI material relevant to the NHT method. The result of this conceptual study is that the steps of the NHT method applied, modified, adapted, and created by PAI teachers consequently and obeyed by their students can increase activeness and learning outcomes simultaneously in PAI lessons.